2010
DOI: 10.1002/mrm.22234
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous B0‐ and B1+‐Map acquisition for fast localized shim, frequency, and RF power determination in the heart at 3 T

Abstract: High-field (!3 T) cardiac MRI is challenged by inhomogeneities of both the static magnetic field (B 0 ) and the transmit radiofrequency field (B 1 1). The inhomogeneous B fields not only demand improved shimming methods but also impede the correct determination of the zero-order terms, i.e., the local resonance frequency f 0 and the radiofrequency power to generate the intended local B 1 1 field. In this work, dual echo time B 0 -map and dual flip angle B 1 1-map acquisition methods are combined to acquire mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 22 publications
3
54
0
Order By: Relevance
“…More generally, the kriging algorithm may help to shorten any MRI sequence, as long as the measured field varies slowly in space. For instance, it may be used for imaging inhomogeneity [37], receive sensitivity [38], or even temperature [39]. The kriging technique can also be used for offline post-processing.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, the kriging algorithm may help to shorten any MRI sequence, as long as the measured field varies slowly in space. For instance, it may be used for imaging inhomogeneity [37], receive sensitivity [38], or even temperature [39]. The kriging technique can also be used for offline post-processing.…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not hold for FA>90°[29] where signals from the edge of the profile can greatly exceed sin( q .θ) at the slice center (Fig. 6)[30]. For full or slab-selective 3D MRI[31], the middle slice of an excited slab is typically unperturbed by the slice profile, and yields accurate results even with short, truncated slab-selective excitation pulses.…”
Section: The ‘Four-fa’ Mri Methodsmentioning
confidence: 99%
“…(10). In addition to a standard ‘sinc’ pulse excitation, the Philips’ scanner can provide ‘spredrex’ excitation pulses (Fig.6a), which have an improved slice profile at high FA across the center of the slice, as compared to a truncated ‘sinc’ pulse (Fig.6d) [30]. A Bloch equation simulation of the effect of slice profile imperfections on T 1 was performed by digitizing ‘spredrex’ pulses into 996 rectangular segments, with the pulse length, amplitude, and gradient strength set according to the scanner’s pulse viewer tool and T 2 =50ms and 100ms.…”
Section: The ‘Four-fa’ Mri Methodsmentioning
confidence: 99%
“…The frequency shift across the heart obtained at 7.0 T compares well with previous 3.0 T studies which reported a peak-to-peak off-resonance variation of (176 ± 30) Hz over the left ventricle and (121 ± 31) Hz over the right ventricle with the use of localized linear and second-order shimming [86]. The use of an enhanced locally optimized shim algorithm, which is tailored to the geometry of the heart, afforded a reduction of the peak-to-peak frequency variation over the heart from 235 to 86 Hz at 3.0 T [87]. Another study showed a peak-to-peak off-resonance of (71 ± 14) Hz for short axis views acquired at 1.5 T [88] using global shimming.…”
Section: Assessment and Control Of Main Magnetic Field Homogeneitymentioning
confidence: 99%